Extracellular proteostasis: an emerging field - Wilson, Mark (Henry Stewart Talks, 2012)
Extracellular proteostasis, Mechanisms of intracellular proteostasis, Disease relevance and potential mechanisms of extracellular proteostasis, Extracellular chaperones, mechanism and abundance, Alpha-2-macroglobulin, Fate of extracellular chaperone-client protein complexes in vivo, Model of extracellular proteostasis, Clusterin can also enter the cytosol (Motor neurone disease)